Information From Same-Race/Ethnicity Experts Online Does Not Increase Vaccine Interest or Intention to Vaccinate - GADARIAN, SHANA KUSHNER; GOODMAN, SARA WALLACE; MICHENER, JAMILA; NYHAN, BRENDAN; PEPINSKY, THOMAS B. (The Milbank quarterly, 2022)
Policy Points Mass vaccination is essential for bringing the COVID‐19 pandemic to a close, yet substantial disparities remain between whites and racial and ethnic minorities within the United States. Online messaging campaigns featuring expert endorsements are a low‐cost way to increase vaccine awareness among minoritized populations, yet the efficacy of same‐race/ethnicity expert messaging in increasing uptake remains unknown. Our preregistered analysis of an online vaccine endorsement campaign, which randomly varied the racial/ethnic identity of the expert, revealed no evidence that information from same race/ethnicity experts affected vaccine interest or the intention to vaccinate. Our results do not rule out the possibility that other low‐cost endorsement campaigns may be more effective in increasing vaccine uptake, but do suggest that public health campaigns might profitably focus on issues of access and convenience when targeting minoritized populations in the United States. Context The COVID‐19 pandemic in the United States has been unequally experienced across racial and ethnic groups. Mass vaccination is the most effective way to bring the pandemic to an end and to manage its public health consequences. But the racialization of public health delivery in the United States has produced a sizable racial/ethnic gap in vaccination rates. Closing this gap in vaccine uptake is therefore essential to ending the pandemic. Methods We conducted a preregistered, well‐powered (N = 2,117) between‐subjects survey experiment, fielded March 24 to April 5, 2021, in which participants from YouGov's online panel—including oversamples of Black (n = 471), Hispanic/Latino/a (n = 430), and Asian American (n = 319) participants—were randomly assigned to see COVID‐19 vaccine information endorsed by same‐ or different‐race/ethnicity experts or to a control condition. We then measured respondents’ vaccination intentions, intention to encourage others to get vaccinated, and interest in learning more information and sharing information with others. Findings Same‐race/ethnicity expert endorsements had no measurable effect on nonwhite or white respondents’ willingness to get the COVID‐19 vaccine, to encourage others to get the vaccine, or to learn more or share information with others. Conclusions Our study provides empirical evidence suggesting online endorsements from same‐race/ethnicity experts do not increase vaccine interest, advocacy, or uptake, though same‐race/ethnicity endorsements may be effective in other venues or mediums.